Expression of p63 in Cervical Intraepithelial Neoplasia (CIN) and Cervical Cancer (Sir Salimullah Medical College Journal, 2022)
Background: Cervical cancer is a major public health problem worldwide. Persistent infection with High-Risk Human Papilloma Virus (HPV) has been the main cause of squamous intraepithelial neoplasia which in turn leads to invasive squamous cell carcinoma. p63 is necessary for the activation of HPV, epithelial proliferation and differentiation. It also regulates the expression of certain cell cycle regulators. It has been reported that, from CIN I to CIN III, p63 expression increases progressively from basal layer to surface. In squamous cell carcinoma, it is expressed throughout the entire thickness of the tumor. Thereby it plays a significant role in diagnosing cervical premalignant and malignant lesions.Objective: To evaluate the relationship of p63 expression with different grades of CIN & invasive SCC.Method: Total 86 paraffin embedded tissue blocks of histopathologically diagnosed cases of CIN and cervical cancer were evaluated by immunohistochemical staining for p63 expression. The study was performed in Sir Salimullah Medical College, Dhaka (from March, 2018 to February, 2020). Statistical analyses were carried out by using SPSS version 22 for Windows. A descriptive analysis was performed for all data. Observations were indicated by frequencies and percentages. Statistical significance was set at “p” value